1999
DOI: 10.1007/s002709900388
|View full text |Cite
|
Sign up to set email alerts
|

Primary stent placement for recanalization of iliac artery occlusions: Using a self-expanding spiral stent

Abstract: A self-expanding spiral stent is a safe and effective device for recanalization of an iliac artery occlusion as the primary stent without any previous intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…On the other hand, Kim et al [15] reported a series of 34 patients presenting with 36 occlusions (mean length 6.92 cm). All lesions were treated with primary stent placement using a self-expanding spiral stent.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Kim et al [15] reported a series of 34 patients presenting with 36 occlusions (mean length 6.92 cm). All lesions were treated with primary stent placement using a self-expanding spiral stent.…”
Section: Discussionmentioning
confidence: 96%
“…A little more than half of the lesions (40, 53%) were between 5 and 10 cm long, while a third (27, 35%) were Ͻ5 cm, and 9 (12%) were Ͼ10 cm in length. The median lesion length was 7 cm (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The reference diameter of the occluded artery was estimated from the diameter of an adjacent or contralaterally patent vascular segment.…”
Section: Patient Populationmentioning
confidence: 99%
“…For total iliac occlusions, a lower risk of distal embolization has been reported when stents are used for primary treatment compared to simple balloon angioplasty. 4 Although there are numerous reports of successful stenting for chronic iliac occlusion, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] only a few studies present their longterm data analyzed on an ''intention-to-treat'' basis. 5,9,16,18 The aim of this retrospective study was to evaluate our results of primary iliac stenting for occlusive lesions in a patient cohort with a Ͼ2-year median follow-up.…”
mentioning
confidence: 99%
“…In some studies courses of long-term anticoagulants were not started routinely [21,25]. ASA was applied by several authors in various dosages (range 100-500 mg daily) in combination with either 250 mg ticlopidine on a lifetime basis, 225 mg dipyridamole for 3-6 months or 250 mg ticlopidine for 3 months [1,15,24]. Funovics et al [17] changed their postinterventional medication regimen from 100 mg ASA daily on a lifetime basis to 75 mg clopidogrel daily later in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Kim et al [24] reported a series of 34 patients presenting with 36 occlusions (mean length 6.92 cm). All lesions were treated with primary stent placement using a self-expanding spiral stent.…”
Section: Discussionmentioning
confidence: 98%